Periodontal Compromised Cases: The Patience and Perseverance That Bears the Fruit - Smruti Bhusan Nanda (Indian Journal of Forensic Medicine & Toxicology, 2020)
Orthodontic treatment in periodontally compromised cases is quite challenging as it involves a thoroughunderstanding of the periodontium keeping given the compromising factors. Bone health plays a pivotalrole in patients opting for orthodontic treatment. Here, we are presenting a case series of periodontallycompromised patients being treated Orthodontically.